2015
DOI: 10.1371/journal.pone.0127184
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of MicroRNAs in Ginkgo biloba var. epiphylla Mak

Abstract: Ginkgo biloba, a dioecious plant known as a living fossil, is an ancient gymnosperm that stands distinct from other gymnosperms and angiosperms. Ginkgo biloba var. epiphylla (G. biloba var. epiphylla), with ovules borne on the leaf blade, is an unusual germplasm derived from G. biloba. MicroRNAs (miRNAs) are post-transcriptional gene regulators that play critical roles in diverse biological and metabolic processes. Currently, little is known about the miRNAs involved in the key stage of partly epiphyllous ovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 74 publications
2
20
0
Order By: Relevance
“…This type of cultivar had previously only been reported growing in Japan. The obtained results are in line with the finding of Zhang et al (2015) who identified a total of 82 miRNA sequences belonging to 23 families and 53 putative novel miRNAs. The expression analysis showed that 25 conserved and 21 novel miR-NAs were differentially expressed between epiphyllous ovule leaves and normal leaves.…”
Section: Resultssupporting
confidence: 90%
“…This type of cultivar had previously only been reported growing in Japan. The obtained results are in line with the finding of Zhang et al (2015) who identified a total of 82 miRNA sequences belonging to 23 families and 53 putative novel miRNAs. The expression analysis showed that 25 conserved and 21 novel miR-NAs were differentially expressed between epiphyllous ovule leaves and normal leaves.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, regulating the MicroRNAs (miRNAs) are a class of endogenous non-coding sRNAs with a size of 21-24 nucleotides (nt) that widely exist in eukaryotes [20,21]. As a negative regulator of gene expression, miRNAs play critical roles in the transcriptional and post-transcriptional regulation of many genes related to plant growth and developmental processes, such as organ morphogenesis, phase change, fruit development, defense against stress, hormone synthesis, and signal transduction [22][23][24][25][26]. In addition, some miRNAs have been identified to play a role in sex determination in plants.…”
Section: Introductionmentioning
confidence: 99%
“…The miRNAs of M. quadrifolia and seed plants identified by Chávez-Montes et al [19] were reanalysed to identify bona fide conserved miRNAs (see Materials and Methods). We also compared P. minima sequences with the miRNAs of various gymnosperms and basal angiosperms [19,[30][31][32][33], as well as conserved miRNAs identified recently in the liverworts Pellia endiviifolia [34] and Marchantia polymorpha [35,36].…”
Section: Ancient Land Plant Mirna Familiesmentioning
confidence: 99%